Spectroscopic, Thermodynamic and Molecular Docking Studies on Molecular Mechanisms of Drug Binding to Proteins - Wani, Tanveer A.; Zargar, Seema; Hussain, Afzal (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains several articles where the molecular mechanisms and structural changes in target proteins on interaction with various viruses and bacteria were studied. In addition, drug-protein interactions, drug-drug interaction mechanisms, anti-Glycating, antioxidant, binding affinity, network pharmacology-driven investigations, and targeted anticancer treatments were also investigated.